Improving Sleep Quality and Well-Being in Institutionalized Older Adults: The Potential of NESA Non-Invasive Neuromodulation Treatment - Aníbal Báez-Suárez; Virginia Báez-Suárez; Laissa Saldanha; Martín Vílchez-Barrera; Andrea Hernández-Pérez; Raquel Medina-Ramírez (Geriatrics)
Background/Objectives: Ageing is associated with several cognitive, physical, and emotional changes, including a decrease in sleep quality and mental health issues. This study studies NESA (Spanish acronym for Neuromodulación Superficial Aplicada) non-invasive neuromodulation using microcurrents as something that may provide a potential improvement in the quality of sleep and general health of older adults and residents in a healthcare institution. Methods: This observational study recruited 24 people who were residents at a long-term care facility. Participants were divided into two groups: one intervention group, who underwent NESA therapy twice a week for a total of 20 sessions, and a control group, who did not receive this treatment. The outcomes measured include sleep quality (Pittsburgh Sleep Quality Index), diary of sleep, symptoms of depressed mood (Yesavage Geriatric Depression Scale), and quality of life with the World Health Organization Quality of Life-Old (WHOQOL-OLD). Scores were collected at baseline, after 10 and 20 sessions, and 3 months after finishing the treatment. Results: The intervention group exhibited a notable improvement in sleep quality (p = 0.05). Additionally, there were fewer nocturnal awakenings. The quality of life also showed better scores, especially in relation to social relations and physical and mental health, which matches the slight decrease in scores and clinical improvement regarding depressive symptoms. In contrast, the control group demonstrated no improvement in symptoms, and in some cases, there was a worsening of symptoms. Conclusions: Our findings indicate that NESA non-invasive neuromodulation therapy is likely to enhance sleep quality and health-related measures in institutionalized older adults. Despite the limitations of the current study, the results support the potential of NESA microcurrents to enhance the well-being of this population.